Naturvorstellungen im Altertum - Naturvorstellungen im Altertum : Schilderungen und Darstellungen von Natur im Alten Orient und in der griechischen Antike / herausgegeben von Florian Schimpf, Dominik Berrens, Katharina Hillenbrand, Tim Brandes, Carrie Schidlo. (Oxford)
ii, 285 sayfa
Keywords: “This volume looks at the concepts of nature in texts as well as in archaeological remains of the Ancient Near Eastern and Greek cultures from the Archaic to the Hellenistic period. Contributions from the fields of archaeology and philology are juxtaposed for each time period in chronological order“ --